Cytokines Profile in Newly Diagnosed Children with Type 1 Diabetes Mellitus - Saleh, Eman M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Cytokines have long been implicated in the pathogenesis of autoimmune diabetes in a number of studies, and playing a role in the initiation of β-cell damaging process. The objective of this study is to gain more understanding about the role of cytokines in initiation of T1DM, through assessment of IFN-γ, IL-10 and IL-6 in diabetic patients.Patients and methods: A total of 60 patients who were newly diagnosed as having T1DM (diagnosed less than five months) were included in the present study. Fifty apparently healthy control subjects were underwent the measurement of serum IFN-γ, IL-10 and IL-6 by ELISA.Results: Higher serum levels of IFN-γ, IL-10, and Il-6 were observed in the investigated patients ≤10 years (75.60, 104.92, 147.6 pg/ml respectively) compared to controls (42.66, 57.01, 80.4 pg/ml respectively). The statistical analysis revealed a significant difference between patients and controls (P1= 0.005, 0.003, 0.036 respectively). The mean levels of serum IFN-γ, IL-10, and Il-6 were also significantly elevated in >10 years old patients (70.78, 84.22, 171.8 pg/ml respectively) than controls (40.39, 59.50, 81.6 pg/ml respectively), (P1= 0.006, 0.037, 0.04 respectively). A statistically difference of mean IL-10 concentration appears between patients in both age groups (P2= 0.04). No significant differences appear in the mean serum concentrations of IFN-γ, and IL-6 between the two age groups (P2=0.73, 0.07 respectively).Conclusions: In children with diabetes, a significant elevation of serum levels of IFN-γ, IL-10 and IL-6 were observed.